Narratives of the Experiences of Indonesian Pre-Service Teachers in Learning Mathematics and Their Relationship with Their Beliefs in Mathematics Teaching - Ramli, Dhitta Puti Sarasvati; Masruroh, Aulia; Tambunan, Nurma (Universitas Teknokrat Indonesia, 2025)
Pre-service teachers’ experiences of learning mathematics in schools is one of the factors that affect their beliefs on mathematics teaching. This study aims to: (1) explore the learning experiences of Indonesian mathematics pre-service teachers prior to their teacher’s training in the university, (2) a analyze the connection between pre-service teachers’ mathematics learning experiences and their belief related to mathematics teaching. The latter includes beliefs about mathematics, learning mathematics and teaching mathematics. Six first year pre-service mathematics teachers studying in Mathematics Education in a private university in Jakarta were interviewed using an in-depth semi-structured interview where they narrated their experiences in learning mathematics and defined their beliefs related to mathematics teaching. This study explains how the past experiences of the pre-service teachers connect with their beliefs related with mathematics teaching. Our findings showed that most participants experience learning mathematics through listening to teachers’ explanations about mathematical concepts and through working on mathematical exercises (drilling). This kind of learning relates with the instrumental and platonic view of mathematics. Consistently, participants in this study show that their beliefs related with mathematics teaching is derived from either the instrumental or platonic view of mathematics, while we did not find any that showed belief from a problem-solving view. This means that the participants believed that mathematics is seen of a set of facts, rules , or skills that is given or it sees mathematics or seen as something fixed and static.